The Yin and Yang of entrepreneurship: Gender differences in the importance of communal and agentic characteristics for entrepreneurs' subjective well-being and performance - Hmieleski, Keith M.; Sheppard, Leah D. (Journal of Business Venturing, 2019)
This research examines gender differences in the relationships of entrepreneurs' agentic and communal personality characteristics with measures of subjective well-being and new venture performance. Results from a stratified national (USA) random sample of founding CEOs (N = 303) demonstrate the advantages of an agentic characteristic (creativity) for women and a communal characteristic (teamwork) for men, with regard to the respective abilities of such persons to achieve high levels of subjective well-being and new venture performance. These relative advantages for women and men were mediated by perceptions of person-work fit.